Chromosome-scale assembly and annotation of the wild wheat relative Aegilops comosa - Hongna Li; Shams ur Rehman; Rui Song; Liang Qiao; Xiaohua Hao; Jing Zhang; Kairong Li; Lifeng Hou; Wanyi Hu; Le Wang; Shisheng Chen (Scientific Data)
Abstract Wild relatives of wheat are valuable sources for enhancing the genetic diversity of common wheat. Aegilops comosa, an annual diploid species with an MM genome constitution, possesses numerous agronomically valuable traits that can be exploited for wheat improvement. In this study, we report a chromosome-level genome assembly of Ae. comosa accession PI 551049, generated using PacBio high-fidelity (HiFi) reads and high-throughput chromosome conformation capture (Hi-C) data. The assembly spans 4.47 Gb, featuring a contig N50 of 23.59 Mb and a scaffold N50 of 619.05 Mb. A total of 39,057 gene models were annotated through a combination of homoeologous proteins, Iso-seq, and RNA-seq data. Comparative genome analysis revealed a terminal intrachromosomal translocation on chromosome 2 M in Ae. comosa. This newly constructed reference genome of Ae. comosa will serve as an important genomic resource for comparative genomic studies and the cloning of agriculturally important genes.